1986
DOI: 10.1001/jama.1986.03380140074025
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cytomegalovirus Infection in Pregnancy

Abstract: We studied 16 218 pregnant women from two income groups to determine the incidence of primary cytomegalovirus (CMV) infection and its consequences for the offspring. In the high-income group, 64.5% of the women were seronegative for CMV and 1.6% had primary CMV infection. In the low-income group, only 23.4% of the women were seronegative for CMV, but 3.7% experienced a primary infection. The rate of transmission in utero was similar in the two groups (39% and 31%). Congenital infections were more frequent in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 748 publications
(116 citation statements)
references
References 28 publications
6
109
0
1
Order By: Relevance
“…26 The high prevalence of CMV detected in this current study is probably due to the biased in selecting stillborn infants as our study population. Nonetheless, our result was expected as CMV is the most common congenital viral infection 27,28 and has been associated with stillbirths in case reports. 29 It is also possible that using sensitive methodologies (PCR and blood on NBSC), we were able to detect more CMV infections.…”
Section: Discussionsupporting
confidence: 53%
“…26 The high prevalence of CMV detected in this current study is probably due to the biased in selecting stillborn infants as our study population. Nonetheless, our result was expected as CMV is the most common congenital viral infection 27,28 and has been associated with stillbirths in case reports. 29 It is also possible that using sensitive methodologies (PCR and blood on NBSC), we were able to detect more CMV infections.…”
Section: Discussionsupporting
confidence: 53%
“…Overall, the vertical transmission rate was found to be 20-40% in pregnant women with primary infection and 0.2-2.2% in previously known seropositive women undergoing recurrent infection during pregnancy [33,34,35,36]. Nevertheless, irrespective of the type of infection, severe congenital infections have been reported and it seems that protection provided by a previous CMV infection is only partial [37,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…In 1986, Stagno et al [34] reported the association between gestational age and the risk of vertical transmission. In this study the authors did not find any difference in the transmission rate when they compared pregnancies where maternal CMV infection occurred between weeks 4 and 22, 16 and 27, and 23 and 40.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations